Imposex in gastropods from Argentina (South-Western Atlantic) - Penchaszadeh, Pablo Enrique (2001)
Imposex is a widespread phenomenon in marine molluscs, documented in more than 120 gastropod species. Its occurrence is explained as a result of an anti-fouling paint compound called TBT (Tributyltin) (Bryan et al., 1986), whose presence is related to high marine traffic.